2010
DOI: 10.1097/ogx.0b013e3181e39b8f
|View full text |Cite
|
Sign up to set email alerts
|

Umbilical Vein Oxytocin for the Treatment of Retained Placenta (Release Study): A Double-Blind, Randomized Controlled Trial

Abstract: The little data that exist on reasons for postpartum readmission after initial hospitalization for delivery have focused primarily on route of delivery rather than specific indications that necessitate readmission. The aim of this study was to investigate indications for postpartum readmission. The study participants were women who delivered during 2007 and were readmitted within 6 weeks of the original delivery discharge date at 114 Hospital Corporation of America hospitals in 21 states. Preliminary data sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The tube was then withdrawn by 5 cm to allow for any divisions of the vein prior to its insertion into the placenta. This method resulted in complete filling of the placental bed capillaries …”
Section: Methodsmentioning
confidence: 76%
See 1 more Smart Citation
“…The tube was then withdrawn by 5 cm to allow for any divisions of the vein prior to its insertion into the placenta. This method resulted in complete filling of the placental bed capillaries …”
Section: Methodsmentioning
confidence: 76%
“…This method resulted in complete filling of the placental bed capillaries. 12 At 30 and 45 min after administration of the medication, or in the case of clinical signs of placental separation, an attempt to deliver the placenta was made. If the final attempt to deliver the placenta (45 min after administration of the study medication) failed, manual removal was performed in the operation theatre.…”
Section: Methodsmentioning
confidence: 99%
“…These guidelines recommend injecting saline-diluted oxytocin into the umbilical vein. However a large, randomized, controlled trial recently reported that the injection had no clinically significant effect on the need to remove retained placenta manually [5].…”
Section: Introductionmentioning
confidence: 99%